2023
DOI: 10.21203/rs.3.rs-2493117/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seismic velocity structure of the crust and the upper mantle beneath the island of Crete, Greece

Abstract: Crete is located in the Southern Aegean, in the southernmost part of the Hellenic Trench. Given the elevated numbers of seismicity in the region generated by the convergence of the Eurasian and African tectonic plates, the research area is critical. More than 1400 manually revised events from 2018 to 2022 have been used in this work to construct both local and regional 1-D velocity models. These data were entered into Passive Seismic Tomography, which is using body-wave (P and S) travel-time data to analyze me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…Several studies have revealed that the maximum depth of seismicity in Kyushu, Japan, is 200 km, while it is about 270 km in the central and southern parts of the island arc [12,[16][17][18]. According to these studies, the subduction zone has a shallow dip angle of about 30 • .…”
Section: Focal Depth Distributionmentioning
confidence: 99%
“…Several studies have revealed that the maximum depth of seismicity in Kyushu, Japan, is 200 km, while it is about 270 km in the central and southern parts of the island arc [12,[16][17][18]. According to these studies, the subduction zone has a shallow dip angle of about 30 • .…”
Section: Focal Depth Distributionmentioning
confidence: 99%